The origins of firm strategy: Learning by economic experimentation and strategic pivots in the early automobile industry - Pillai, Sandeep D.; Goldfarb, Brent; Kirsch, David A. (Strategic Management Journal, 2020)
Abstract Research Summary We explore the effectiveness of economic experimentation as a learning mechanism through a historical exploration of the early automobile industry. We focus on a particular subset of economic experiments, called strategic pivots, that requires irreversible firm commitments. Our quantitative analysis suggests that strategic pivoting was associated with success. We then use historical methods to understand whether this association is reasonably interpreted as a causal link. We identify lessons that could only plausibly have been learned through strategic pivoting and document that those firms that were able to learn from the strategic pivots were most likely to succeed. We discuss the generalizability of our findings to build the hypothesis that strategic pivots and economic experiments originate firm strategy. Managerial Summary We explore the effectiveness of experimentation as a learning mechanism through a historical exploration of the early automobile industry. We focus on a particular subset of experiments, called strategic pivots, that requires irreversible firm commitments. Our analysis suggests that strategic pivoting was associated with success. We identify lessons that could only plausibly be learned through strategic pivoting and document that those firms that were able to learn from the strategic pivots were most likely to succeed. Even though firms may use lean techniques, market solutions may only be discovered through strategic pivots whose outcomes are unknowable ex‐ante. Therefore, successful strategies reflect an element of luck.